TANGGUNGJAWAB PERDATA PEMILIK PERSEROAN TERBATAS (PT) TERHADAP KERUGIAN PIHAK LAIN DALAM TINJAUAN HUKUM BISNIS ISLAM - Wahid Hadi Purnomo (Maliyah : Jurnal Hukum Bisnis Islam, 2015)
The existence of Limited Company (LC) in business is a necessity. Limited Company in Indonesia is regulated by Undang-Undang Nomor 40 Tahun 2007. The domination of the company in the form of Limited Company is because of its superiority in comparison with other forms of company. The first advantage, Limited Company provides easiness to transfer its shares to other parties or persons. The second, shareholder liability of Limited Company is limited to the value of shares held in the Limited Company itself. The enthusiasts of LC are not only from among non-Muslims but also Muslim investors who are choosing it as a form of business entity to run their business. Muslim businessmen, other than as a citizen of Indonesia who are supposed to be the subject to the rules of positive law in Indonesia, including the law pertaining to company, should also be the subject to the provisions of shari'ah. In relation with the discussion above, there are some fundamental questions as follow; (1) is there any kinds of legal form of Limited Company in Islam?; (2) is there any limitations of liability in Islam?; (3) is the limitation of liability is allowed under Islamic law?. Based on the research, it can be concluded that Islam does not have the shirkah system which has the similarities to Limited Company of either in the form of responsibility or its legal status. According to al-Qur’an and al-hadith that each individual is responsible to pay all debt dependents without any restrictions. Islam does not also allow a form of limited obligation as set out in Limited Company. It is because the provisions of shari>'ah states that one should not reduce a bit of his or her own debt.